Implementation of Project Based Learning Model to Improve Elementary School Students' Learning Outcomes in Science Learning - Desca Saurina; Fitri Nuraeni; Nenden Permas Hikmatunisa (Penerbit Hellow Pustaka, 2025)
Learning Natural Science (IPA) class IV A at SDN Palumbosari II is thought to be inadequate due to the lack of student participation and involvement in the learning process, which ultimately results in less than optimal student learning outcomes. This research was conducted with the aim of knowing the progress of student and teacher activities and improving optimal student learning outcomes. The Project Based Learning Model is a project or activity based learning model as a medium. Students are assigned to explore, interpret and evaluate information to improve learning outcomes. The research method uses classroom action research methods. Research conducted on class IV A students at SDN Palumbosari II showed improvement after going through two learning cycles. Initially it was thought that the science learning process in class IV A had not been implemented well, the teacher improved it by implementing the Project Based Learning model which made students more active and directly involved in the learning process. From the implementation of this class action, it was concluded that the application of the Project Based Learning model in science learning was said to be successful in improving the learning outcomes of class IV A students at SDN Palumbonsari II.